Fluxo de metano no bioma Pampa: análises em área de arroz e de pecuária - Maboni, Cristiano (2021)
Methane (CH4) is approximately 28 times more efficient at absorbing radiation than carbon dioxide (CO2), potentiating global warming. In this way, the production systems that emit CH4 have special attention in studies that quantify and mitigate these emissions. Several methodologies have been used to quantify these emissions. However, the Eddy Covariance (EC) methodology is the state of the art in these estimates as it incorporates all exchanges of these gases in an ecosystem. In agriculture, rice production and livestock are the main emitters of CH4. In this thesis, these two production systems will be evaluated in relation to CH4 emissions through the EC methodology. The studies are conducted at two experimental sites within the Pampa Biome in the state of Rio Grande do Sul - RS, Brazil. Measurements of CH4 emissions were carried out for nine months in a flooded irrigated rice area in the municipality of Cachoeira do Sul (and extrapolated to the annual period) and for two and a half years in a rotational management of cattle in a field pasture native in the municipality of Aceguá - RS. The annual emission in the rice area was 43.87 gCH4 m-2 year-1, and the rice cultivation emitted 33.03 gCH4 m-2, three times greater than the period without rice (fallow). These results show that the estimates of the Intergovernmental Panel for Climate (IPPC-2006) underestimate CH4 emissions by 30% for rice cultivation in this region. In an average of two years, the livestock area emitted 3.75 gCH4 m-2 year-1, with CH4 emissions due to cattle representing approximately 60% of annual emissions. Thus, CH4 emissions in rice are around 12 times higher than in livestock. As these systems also exchange other greenhouse gases in the atmosphere, such as CO2, estimates of these exchanges were also used to estimate the total annual global warming potential (GWP), considering the consumption of harvested rice or the meat of the cattle produced, converting the variables into CO2 equivalent (CO2-eq). CO2 is the main component of GWP in both systems, and is absorbed in both. However, rice was a GHG emitter (GWP = 1539.42 gCO2-eq m-2), and fallow was responsible for 90% of this value, while livestock in the native field was a GHG absorber (GWP = - 76.5 gCO2-eq m-2). These unprecedented results may become the basis for public policies for offsetting GHG emissions and for future work to mitigate these gases in the Brazilian Pampa Biome.